Carbon Footprint Assessment of a Combined Cycle Gas Turbine (CCGT) Power Plant from a Life Cycle Perspective: A Case Study of Energy Transition in Indonesia - Yustitia, Fortunita Nindia; Megasari, Ni Luh Ayu; Hargono, Arief; Iswara, Aditya Prana (Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Climate change, driven by greenhouse gas (GHG) emissions, necessitates transformative shifts in the global energy sector. This is particularly critical for Indonesia, which continues to rely heavily on fossil fuels. In this context, Combined Cycle Gas Turbine (CCGT) power plants have emerged as a potential transitional technology, offering higher efficiency and lower operational emissions than coal-fired power plants. This study employs a Life Cycle Assessment (LCA) framework to analyze the carbon footprint of a CCGT power plant in Indonesia, providing a comprehensive evaluation of its environmental impacts across all stages—from fuel extraction to plant operation and electricity distribution. The findings reveal that the natural gas combustion process and upstream gas production are the primary contributors to the total emissions, accounting for approximately 0.473 kg CO₂-eq/kWh and 0.26 kg CO₂-eq/kWh, respectively. Despite these emissions, the CCGT plant demonstrates a significantly lower carbon footprint compared to coal-fired power generation. The study also identifies key strategies for mitigating emissions, including enhancing methane leak detection technologies, optimizing natural gas transportation, and integrating Carbon Capture and Storage (CCS). Based on these findings, we provide technical and policy recommendations to support a sustainable energy transition in Indonesia.